The influence of sports on proactive personality and academic achievement of college students: The role of self-efficacy - Li, Xinnan; Liu, Min; Yu, Haofei; Zhang, Zhanjia; He, Zhonghui (Frontiers in Psychology, 2022)
Objective: To explore the mediating effect of self-efficacy on the relationship between the proactive personality and academic performance of college students in different sports groups. Methods: A questionnaire survey is used to study 552 college students. The research tools include the proactive personality scale, the self-efficacy scale table (general, academic, and self-regulation efficacy scale tables), and the academic performance self-report scale table. This research employs SPSS 11.0 statistical software to carry out correlation analysis, regression analysis, and T-tests on the data collected, while the test of mediating effect is carried out by AMOS 22.0. Results: (1) The degree of self-efficacy and academic performance of college students participating in physical activities is significantly greater than that of the non-sports group; (2) the proactive personality level of the sports group is significantly higher than the non-sports group in the dimension of “conscientiousness”; (3) a confirmatory factor analysis of the mediating effect hypothesis model, using the structural equation model, found that self-efficacy plays a full mediating role in the relationship between proactive personality and academic performance; the direct effect of self-efficacy on the proactive personality and academic performance of college students in different sports groups is not significant. Conclusion: College students involved in sports exercise have higher scores on some items about proactive personality than non-sports groups; girls’ self-efficacy level is higher than that of boys; self-efficacy plays a full mediating role in the relationship between proactive personality and academic performance; self-efficacy had no significant effect on proactive personality and gender in different sports groups.